ANTIAGEING POTENTIALS OF PLANT METABOLITES: A REVIEW - Abhishek Srivastava (International Journal of Phytomedicine, 2025)
Abstract Ageing, a medically unsolved mystery, is a multifactorial process that causes cells, tissues, and organisms to gradually lose their functional capacity. Although it is impossible to stop ageing, it is entirely feasible to slow down the rate of ageing. Ageing is a multi-faceted molecular process exacerbated by various molecular pathways and biochemical processes supported by both environmental and genetic factors. These effects are a result of the stressors that accumulate over time as we age, causing biomolecules to become more and more damaged and ultimately compromising cellular homeostasis. Redox imbalance and oxidative stress are intrinsically linked to ageing and ageing-related diseases like cardiovascular disease, cancer, diabetes, and neurodegenerative disorders, which have exponentially increased in prevalence. The significance of herbs and herbal products is becoming more widely understood. Due to their extraordinary potential in the treatment and prevention of oxidative stress-related disorders, plants and their botanical preparations have been used for centuries. Each entire plant matrix contains hundreds of biologically active components that promise to positively affect. The use of contemporary scientific methods has recently been used to document the role of herbal medicines, herbal products, and specific phytochemicals in the prevention of ageing. This review focuses on some natural substances that have potent anti-ageing properties and can be used to treat a number of age-related neurological disorders. A number of substances, including phenolics, carotenoids, terpenoids, and alkaloids, may play a significant role as antioxidants and free radical scavengers. These ingredients can be found in fruits, seeds, leaves, or roots.